2018
DOI: 10.1093/nar/gky347
|View full text |Cite
|
Sign up to set email alerts
|

Sin3a–Tet1 interaction activates gene transcription and is required for embryonic stem cell pluripotency

Abstract: Sin3a is a core component of histone-deacetylation-activity-associated transcriptional repressor complex, playing important roles in early embryo development. Here, we reported that down-regulation of Sin3a led to the loss of embryonic stem cell (ESC) self-renewal and skewed differentiation into mesendoderm lineage. We found that Sin3a functioned as a transcriptional coactivator of the critical Nodal antagonist Lefty1 through interacting with Tet1 to de-methylate the Lefty1 promoter. Further studies showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 58 publications
1
64
0
Order By: Relevance
“…While our manuscript was under revision, Zhu et al . 30 , reported the binding site of Tet1 to the Sin3A PAH1 domain, and found that the Tet1/PAH1 association was required for ES cell pluripotency. Sin3A helps recruit Tet1 to genes such as the Nodal antagonist, Lefty1, maintaining its transcriptional activity and thus preventing commitment towards a mesendodermal lineage 30 .…”
Section: Discussionmentioning
confidence: 99%
“…While our manuscript was under revision, Zhu et al . 30 , reported the binding site of Tet1 to the Sin3A PAH1 domain, and found that the Tet1/PAH1 association was required for ES cell pluripotency. Sin3A helps recruit Tet1 to genes such as the Nodal antagonist, Lefty1, maintaining its transcriptional activity and thus preventing commitment towards a mesendodermal lineage 30 .…”
Section: Discussionmentioning
confidence: 99%
“…RNA expression in cerebral cortex (neuronal, glial and endothelial cells), thyroid and parathyroid glands (glandular and endothelial cells), smooth muscle cells, gallbladder, male and female reproductive tracts Active DNA demethylation by catalytic conversion of 5methylcytosine (5mC) into 5hydroxymethylcytosine (5hmC) [33] Chromatin regulation by O-linked N-acetylglucosamine transferase recruitment to transcriptional start sites promoting histone H2B GlcNAcylation [188] Involved in trophoblast stem cell maintenance and integrity, and cell-cycle progression [189] Transcriptional regulation via interaction with the transcriptional corepressor, SIN3A [190] Upregulated in inflammatory microenvironment of hyperinsulinemia and invasive ductal carcinoma [191].…”
Section: Tet 1 (Methylcytosine Dioxygenase 1)mentioning
confidence: 99%
“…Shared demethylation and chromatin regulation role with other TET family members [36,37,48,190] Regulates hematopoietic stem cell (HSC) self-renewal, haematopoiesis and myeloid lineage commitment and differentiation. [197] TET2 is targeted by microRNA-22 to regulate HSC self-renewal and transformation [198] Involved in trophoblast stem cell maintenance and integrity [189] Somatic TET2 mutations altering the enzymes catalytic activity observed in many cancers (myelodysplasia, AML, breast, lung, pancreas and liver [52, 196, 199-201]) 4q24 (Tet2) is a common chromosomal deletion observed in hematopoietic malignancies.…”
Section: Tet 2 (Methylcytosine Dioxygenase 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Tet1 in particular forms protein:protein interactions with other epigenetic complexes, adding an additional layer of potential regulation. For example, Tet1 directly interacts with Sin3a[25], a core component of the repressive histone-deacetylase complex. Genes co-occupied by both Tet1 and Sin3a, such as Lefty1 appear to be activated by the presence of both proteins, indicating that the combinatorial interaction of different epigenetic complexes must be examined in combination to truly appreciate their effects on gene expression.…”
mentioning
confidence: 99%